2017
DOI: 10.3788/col201715.081901
|View full text |Cite
|
Sign up to set email alerts
|

Matrix formalism for radiating polarization sheets in multilayer structures of arbitrary composition

Abstract: In optical studies on layered structures, quantitative analysis of radiating interfaces is often challenging due to multiple interferences. We present here a general and analytical method for computing the radiation from two-dimensional polarization sheets in multilayer structures of arbitrary compositions. It is based on the standard characteristic matrix formalism of thin films, and incorporates boundary conditions of interfacial polarization sheets. We use the method to evaluate the second harmonic generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…We studied the silicon (Si) /silica/water layer structure, with the near-infrared at 800 nm and broadband infrared centered at 1000 cm − 1 to match the Si-O stretch range. Using the nonlinear optical matrix formalism to calculate the eld distributions across the layer structure 34,36 , we found that despite the strong infrared attenuation in silica, the total SF response from the silica/water interface could be drastically enhanced if the silica lm thickness was near 150 nm (Fig. 1b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We studied the silicon (Si) /silica/water layer structure, with the near-infrared at 800 nm and broadband infrared centered at 1000 cm − 1 to match the Si-O stretch range. Using the nonlinear optical matrix formalism to calculate the eld distributions across the layer structure 34,36 , we found that despite the strong infrared attenuation in silica, the total SF response from the silica/water interface could be drastically enhanced if the silica lm thickness was near 150 nm (Fig. 1b).…”
Section: Introductionmentioning
confidence: 99%
“…1b). Meanwhile, the response from the silicon/silica interface remained low, ensuring the SF output to be dominantly from the silica/water interface 34,35 (see Supplementary Section 1.2). We prepared the 150 nm amorphous silica lm on an n-type Si wafer by plasma-enhanced chemical vapor deposition (see Methods).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation